ISLAM, SUMBER DAYA MANUSIA, DAN MOTIVASI KERJA: DINAMIKA KINERJA PERANGKAT DESA SE-KECAMATAN WONGSOREJO BANYUWANGI - Andhika Wahyudiono (Jurnal MD, 2017)
Humans descended as a khalifa on earth that one of its duties is to realize the prosperity of the ummah. In the context of Indonesia, one of the roles of khalifa is manifested in a governmental structure such as a village apparatus. Of course in carrying out the task a khalifa should have high motivation of work as a form of professionalism like the hadith narrated by Ahmad. This study aims to determine the relevance of human resource and work motivation in the performance dynamics of village office apparatus in Wongsorejo Subdistrict either partially or simultaneously. The population in this study is the government officials in the villages in entire Wongsorejo sub-district consists of 12 villages totaling 206 with a sample of 103 people selected by proportional random sampling. And then the data is analizing by using multiple linear regression analysis. The result of the research shows that the positive and significant influence of human resources and work motivation has significant effect to the performance dynamics either partially or simultaneously. The influence of human resources and work motivation to the dynamics of performance are by 42 percent.